2014
DOI: 10.1007/s00256-014-1991-6
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular anteversion is associated with gluteal tendinopathy at MRI

Abstract: Our MRI study suggests that there is an association between increased AA and gluteal tendinopathy, which supports a growing body of evidence implicating abnormal biomechanics in the development of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“… 1 , 2 Additionally, it is reported that abnormal acetabular anteversion and/or femoral version participate in the etiogenesis of hip osteoarthritis, 3 , 4 developmental dysplasia of the hip (DDH), 5 , 6 and gluteal tendinopathy. 7 Femoral neck-shaft angle, defined as an intersection angle by proximal femoral shaft axis and femoral neck axis, is another clinically significant parameter of proximal femoral geometry (PFG). Recent studies 8 , 9 indicate that a greater neck-shaft angle may increase the risk of proximal femoral fracture.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Additionally, it is reported that abnormal acetabular anteversion and/or femoral version participate in the etiogenesis of hip osteoarthritis, 3 , 4 developmental dysplasia of the hip (DDH), 5 , 6 and gluteal tendinopathy. 7 Femoral neck-shaft angle, defined as an intersection angle by proximal femoral shaft axis and femoral neck axis, is another clinically significant parameter of proximal femoral geometry (PFG). Recent studies 8 , 9 indicate that a greater neck-shaft angle may increase the risk of proximal femoral fracture.…”
Section: Introductionmentioning
confidence: 99%
“…8 This spawned several studies seeking to correlate radiographic findings with the presence of GTPS. 7,13 Fearon et al 7 examined differences in the femoral neckshaft angle, acetabular index, pelvic width, distance between the trochanters, and hip circumference (adiposity) in 220 women, concluding that a neck-shaft angle lower than 134 and increased adiposity were risk factors. A closer examination of their analysis, however, raises some doubts about the strength of these associations.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 Moulton et al showed that an increased acetabular anteversion is associated with tendinopathy of the gluteus minimus and medius as well as with trochanteric bursitis. 50 On US, tendinosis is defined by tendon thickening and heterogeneous hypoechogenicity due to edema. Peritendinous hyperemia may be demonstrated by color Doppler.…”
Section: Extra-articular Injuries Greater Trochanteric Pain Syndromementioning
confidence: 99%